2019
DOI: 10.1007/s00420-019-01426-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of heat stress and cumulative incidence of acute kidney injury in sugarcane workers in Guatemala

Abstract: Objective Agricultural workers worldwide exposed to heat stress could be at the risk of kidney injury, which could lead to chronic kidney disease of an unknown origin (CKDu). Hydration has been promoted as a key measure to reduce kidney injury. In the presence of a hydration intervention, the incidence of acute kidney injury (AKI) was calculated in a sugarcane worker population in Guatemala and several risk factors were evaluated. Methods We measured kidney function at the beginning and end of the work shift a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
104
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(122 citation statements)
references
References 28 publications
7
104
2
1
Order By: Relevance
“…Hyperuricemia has been associated with kidney dysfunction in cross-sectional studies (30,46,47,71), tentatively as part of the pathophysiological pathway compatible with an occupational heat stress etiology (72). Consumption of NSAIDs, which also can be seen as occupationally related if used because of musculoskeletal pain in hard manual labor, yielded negative results in all studies, except for an interaction with pre-shift dehydrated state for acute kidney injury in a Guatemalan cross-shift study in sugarcane field workers (50), and there are no consistent observations for other nephrotoxic pharmaceuticals. Alcohol, illegal alcohol and tobacco were inconsistently related to low kidney function in prevalence studies.…”
Section: Non-occupational Risk Factorsmentioning
confidence: 94%
See 2 more Smart Citations
“…Hyperuricemia has been associated with kidney dysfunction in cross-sectional studies (30,46,47,71), tentatively as part of the pathophysiological pathway compatible with an occupational heat stress etiology (72). Consumption of NSAIDs, which also can be seen as occupationally related if used because of musculoskeletal pain in hard manual labor, yielded negative results in all studies, except for an interaction with pre-shift dehydrated state for acute kidney injury in a Guatemalan cross-shift study in sugarcane field workers (50), and there are no consistent observations for other nephrotoxic pharmaceuticals. Alcohol, illegal alcohol and tobacco were inconsistently related to low kidney function in prevalence studies.…”
Section: Non-occupational Risk Factorsmentioning
confidence: 94%
“…Cross-shift evaluations have been conducted in sugarcane cutters in Costa Rica, Nicaragua, El Salvador and Guatemala. Without exception, these studies concluded that cross-shift physiologic and biomarker changes were compatible with recurrent dehydration from strenuous work in hot environments (45)(46)(47)(48)(49)(50). Three studies examining multiple cross-shifts documented repeated dehydration over the day (45,47,48).…”
Section: Analytical Epidemiologic Studies Highlight Occupational Heatmentioning
confidence: 99%
See 1 more Smart Citation
“…This research was conducted in a prospective cohort of male sugarcane field workers in Guatemala in 2016-17. The study is de-scribed in detail elsewhere [9,10]. A schematic of the study timeline is provided in the online supplement Figure S1 (for all online suppl.…”
Section: Setting and Participantsmentioning
confidence: 99%
“…Because AKI is a known complication in outdoor workers who are hospitalized with HRIs, it is likely that SIR substantially undercounts work-related AKI cases if they are classified only as "heat exhaustion." 12,21,22 Furthermore, the SIR database excludes HRIs that were not severe enough to require inpatient hospitalization. Our analysis also excluded many smaller, delivery companies that may employ untrained workers who may also be at risk.…”
Section: Heat Illness and Renal Injury In Mail And Package Delivery Wmentioning
confidence: 99%